PENGARUH GREEN HRM (HUMAN RESOURCES MANAGEMENT) DAN GREEN DIGITAL TECHNOLOGY TERHADAP PERFORMANCE KARYAWAN MELALUI WORK ENGAGEMENT(STUDI PADA BANK INDONESIA BALIKPAPAN) - Clift Allegra Palenewen; Euis Soliha (ITB AAS Indonesia Surakarta, 2025)
This study investigates the mediating role of Work Engagement in the relationship between the implementation of Green Human Resource Management (Green HRM) and Green Digital Technology with Employee Performance at Bank Indonesia, Balikpapan. Adopting a quantitative methodology, this research gathered primary data from 133 employees selected through simple random sampling. The data were subsequently analyzed using path analysis with multiple linear regression. The analysis revealed that Work Engagement is significantly and positively influenced by the adoption of both Green HRM and Green Digital Technology. Furthermore, Work Engagement was proven to be a significant predictor of enhanced Employee Performance. The study's central finding highlights the mediating function of Work Engagement. It was found that Work Engagement partially mediates the link between Green HRM and Employee Performance. In contrast, Work Engagement acts as a full mediator for the relationship between Green Digital Technology and Employee Performance, which is demonstrated by the direct influence of Green Digital Technology on performance becoming non-significant when Work Engagement was included in the analysis model. The implication is that the success of green initiatives in boosting performance is highly dependent on an organization's ability to cultivate work engagement, as this engagement serves as the crucial psychological process that transforms green policies into superior performance outcomes. Keywords: Green HRM, Green Digital Technology, Work Engagement, Employee Performance, Mediation.